2015
DOI: 10.5114/wiitm.2015.54224
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Roux-en-Y gastric bypass with ileal transposition - an alternative surgical treatment for type 2 diabetes mellitus and gastroesophageal reflux.

Abstract: Currently, type 2 diabetes mellitus (T2DM) is considered as a gastrointestinal disease. Numerous studies have demonstrated that bariatric operations ameliorate T2DM significantly. The laparoscopic Roux-en-Y gastric bypass (L-RYGB) is considered as the gold standard procedure. We aimed to evaluate the feasibility and impact of L-RYGB with ileal transposition (or interposition) on diabetes resolution in a patient who has not benefited from any medical therapy, with its additional effect on the amelioration of ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 18 publications
1
5
0
Order By: Relevance
“…(12)(13)(14) In a study comparing the effect of RYGB with that of sleeve gastrectomy, it was found that RYGB reduced all lipid fractions, whereas LDL did not improve significantly in patients who underwent sleeve gastrectomy. (15) The benefits of bariatric surgery on weight loss and glycaemic control have been studied, (16)(17)(18)(19) and our results were consistent with the published literature: there was sustained weight loss and improved glycaemic control at the one-and five-year intervals. The significant improvement in glycaemic level is attributed to a myriad of factors, including changes in absorption of metabolites after surgery and changes in gut-related hormones leading to increased insulin sensitivity and associated weight loss.…”
Section: Discussionsupporting
confidence: 89%
“…(12)(13)(14) In a study comparing the effect of RYGB with that of sleeve gastrectomy, it was found that RYGB reduced all lipid fractions, whereas LDL did not improve significantly in patients who underwent sleeve gastrectomy. (15) The benefits of bariatric surgery on weight loss and glycaemic control have been studied, (16)(17)(18)(19) and our results were consistent with the published literature: there was sustained weight loss and improved glycaemic control at the one-and five-year intervals. The significant improvement in glycaemic level is attributed to a myriad of factors, including changes in absorption of metabolites after surgery and changes in gut-related hormones leading to increased insulin sensitivity and associated weight loss.…”
Section: Discussionsupporting
confidence: 89%
“…Both procedures involve the exclusion of the duodenum from the digestive process and this mechanism was assumed to be required the effect of the operation, which has been confirmed by experimental studies by Rubino and Marescaux [30]. However, another anatomical effect of these operations is the accelerated discharge of partially digested nutrients and their contact with the distal segment of the small intestine, the ileum, which contributes to the secretion of peptides of intestinal origin involved in glucose homeostasis [9].…”
Section: Effect Of Bariatric Operations On Glucose Metabolismmentioning
confidence: 94%
“…Such operations are often referred to as metabolic operations because of their positive effects: weight loss and improved metabolic control, especially in patients with DM2. Obviously, these effects have allowed several authors to consider a bariatric surgery as an alternative to pharmacological treatment, which can help to correct overweight, control hyperglycaemia, and achieve remission of the disease [9][10][11][12][13][14][15][16][17][18][19][20]. A number of studies have shown that surgical methods were successful and improved the condition of patients with diabetes mellitus of type 1 (DM1) [21][22][23] (Table 1).…”
Section: Effect Of Bariatric Operations On Glucose Metabolismmentioning
confidence: 99%
“…In clinical settings, sleeve gastrectomy (SG) and ileal transposition (IT) surgery are the most effective therapies for diabetes control [10,11] and could keep normal insulin levels, plasma glucose concentrations, and glycosylated hemoglobin levels at 80% to 100% of normal range for morbidly-obese patients [9,12]. Moreover, previous studies have indicated that not only SG and IT surgery, but also other bariatric surgeries, might trigger an obvious and satisfactory clinical improvement and outcomes for patients with type 2 diabetes [8,13,14]. However, in the clinical setting, there is controversy regarding which surgical approach to select for treating diabetes.…”
Section: Introductionmentioning
confidence: 99%